2020
DOI: 10.1016/j.immuni.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a SARS-CoV-2-Infected Individual Reveals Development of Potent Neutralizing Antibodies with Limited Somatic Mutation

Abstract: Highlights d Early B cell responses to SARS-CoV-2 spike protein are analyzed from a COVID-19 patient d Most antibodies target non-neutralizing epitopes outside the RBD d A potent neutralizing mAb blocks the interaction of the S protein with ACE2 d Neutralizing antibodies are minimally mutated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
418
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(463 citation statements)
references
References 45 publications
40
418
2
Order By: Relevance
“…5) and the rapid development of potent virus neutralizing antibody responses in macaques after a single dose suggested a minimal requirement for somatic hypermutation (SHM) of the response. This is consistent with recent data showing that neutralizing monoclonal antibodies isolated from SARS CoV-2 convalescent individuals display low levels of SHM 12,27,28 . The polyclonality, antibody germline VDJ usage, and level of SHM that characterizes vaccine-induced SARS CoV-2 spike-induced antibody responses will be a matter of interest, both in the macaque model and in human vaccine trials.…”
Section: Resultssupporting
confidence: 93%
“…5) and the rapid development of potent virus neutralizing antibody responses in macaques after a single dose suggested a minimal requirement for somatic hypermutation (SHM) of the response. This is consistent with recent data showing that neutralizing monoclonal antibodies isolated from SARS CoV-2 convalescent individuals display low levels of SHM 12,27,28 . The polyclonality, antibody germline VDJ usage, and level of SHM that characterizes vaccine-induced SARS CoV-2 spike-induced antibody responses will be a matter of interest, both in the macaque model and in human vaccine trials.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, although no sequence variance was observed on M protein from all sequenced COVID-19 cases, two consecutive mutations (K203RR204G) were found in the highly conserved serine-rich linker Eleven and seventeen epitope regions epitopes were found to elicit neutralization antibodies that inhibit the cell entry of D614 and G614 pseudo-virus, respectively. The antibodies induced by four epitopes (S406-420, S439-454, S455-469, and S475-499) but not S366-381 or S495-509 in RBD region exhibited neutralization effect on both D614 and G614 pseudo-virus, which is consistent with the interaction interface between SARS-CoV-2 receptor-binding motif (RBM) and ACE2 (Seydoux et al, 2020;Shang et al, 2020), indicating that these epitopes are suitable for designing universal vaccines. Previous report showed that a cryptic epitope in the trimeric interface of S protein induced neutralization antibodies for SARS-CoV but not SARS-CoV2.…”
Section: Discussionsupporting
confidence: 61%
“…Second, plasma from the majority of COVID-19 convalescent patients does not contain high levels of neutralizing activity (41). Third, plasma antibodies in infected individuals that do develop neutralizing antibodies are minimally mutated (42). These data suggest that CD8 T cells may contribute to the control of SARS-CoV-2, and while a protracted germinal center response may not be critical for the generation of neutralizing antibodies it could improve antibody durability by enhancing plasma cell numbers.…”
Section: Humoral Responses To Sars-cov-2 Are Dominated By Igg Antibodiesmentioning
confidence: 97%